Understanding well-being in varied students of inclusive classrooms - Bernadetha Haule, Daigo; Husseni Barantota, Siraju; Amirrachman, R. Alpha; Sanga, Amitile Pius (Indonesian Journal of Education and Pedagogy, 2025)
This qualitative case study establishes an investigation into the psychosocial welfare of students with learning differences who receive education in the inclusive classrooms of Madania School located in Bogor, Indonesia. The study evaluates inclusive practice mechanisms through PERMA and Maslow's hierarchy of needs to understand their impact on students' emotional, social, and academic welfare. The researchers conducted in-person interviews as well as direct observations with students, faculty staff and administrative officials during their data collection stage. The results reveal that students at Madania School experience social inclusion with healthy emotional development and psychological security because of their favourable classrooms, caring teacher actions, and efficient bullying prevention strategies. The mentioned factors minimize negative elements while helping students reach their objectives of self-actualization.